1992
DOI: 10.1079/bjn19920121
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Δ9 desaturase (EC1.14.99.5) enzyme activity in growing rat during dietary protein restriction

Abstract: The effects of protein restriction on A9 desaturase (EC 1.14.99.5) activity were studied in growing rats. A control group was fed on a balanced diet (200 g caseinlkg; BD) for 28 d. The experimental group was fed on the low-protein diet (20 g caseinlkg; LP) for 26 d, then refed the balanced diet (BD-R) for 2 d. Rats were born to and suckled from normally fed dams. The enzyme activity was measured after 2 and 14 d of LP, and 26 d of L P plus 2 d of BD-R, by incubations in vitro of hepatic microsomal pellets with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
3
6
0
Order By: Relevance
“…First, we chemically as well as histologically demonstrated the formation of fatty liver in rats fed the lowprotein diet (28)(29)(30). Impaired liver functions (31) in rats fed a protein-restricted diet were also confirmed in the present study, as shown by the decreased level of serum albumin and increased level of serum AST activity.…”
Section: Discussionsupporting
confidence: 80%
“…First, we chemically as well as histologically demonstrated the formation of fatty liver in rats fed the lowprotein diet (28)(29)(30). Impaired liver functions (31) in rats fed a protein-restricted diet were also confirmed in the present study, as shown by the decreased level of serum albumin and increased level of serum AST activity.…”
Section: Discussionsupporting
confidence: 80%
“…Cells were then collected, and total lipids were extracted according to Bligh and Dyer method for saponification and esterification. Radiolabelled fatty acid methyl esters were then separated by RP-HPLC and detected on line by a radioisotope detector (Packard Flow Scintillation Analyser, PerkinElmer Life Sciences Inc., Wellesley, MA) (Narce et al 1992 Western blotting Cells were washed with ice-cold PBS and lysed in ice-cold Ripa buffer containing protease inhibitor cocktail (Sigma) for 15 min on ice. We cleared protein lysate by centrifugation at 10,0009g for 10 min at 4°C.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…Before enzyme activity measurement, [1-14 C]stearic acid (1-14 C 18:0; 50 mCi/mmol, 98% pure; NEN Life ProductsFrance SA, Le Blanc Mesnil, France) was diluted in ethanol (Prolabo, Paris, France) to a specific activity of 5 mCi/mmol with the corresponding unlabeled fatty acid (Sigma Chemical Co, St. Louis, MO). Under such conditions the reaction was linear, proportional to the time of incubation and protein concentration (26). Before the incubation, the microsomes were preincubated at 37°C for 3 min.…”
Section: Animals and Dietsmentioning
confidence: 99%